LEARNING MOTIVATION OF STUDENTS ON SCIENCE SUBJECT THROUGH ONLINE LEARNING AT MTsN 3 PASAMAN BARAT - Meisy Sucia Dinata; Usmeldi Usmeldi (Department of Science Education, 2021)
Using technology in education field can create the interesting ambiance studying and also communicative between teacher and students. One of using technology information Online Learning. Online learning is very helpful to increase studying activities. It is coused by students as millennial generation, they like things that is easy to get. Students cas access anywhere and anytime use their smartphone. Online learning can increase the learning motivation from students. Online learning provides the interesting learning features. The type of this research is descriptive quatitative. The aims of this research is to know the motivation learning students through Online Learning in Students on Science Field at MTsN 3 Pasaman Barat. The technique of sampling is random sampling that involve 60 respondence from students. Analysing data of this research uses SPSS 16.0 for windows. In this research is discovered that the learning motivation of Science Field at MTsN 3 Pasaman Barat included in medium category